Analysis of Work From Home System On Employee Performance of Wilmar International - Devira Devira; Agung Surya Dwianto (Universitas Jabal Ghafur, 2023)
The purpose of this study is to see how the work from home programme has affected employees' working conditions at PT Wilmar International, a global agricultural company. It is crucial to understand how the work from home policy affects employee performance to increase the adoption rate. This research uses a qualitative approach methodology through in-depth interviews. The findings of this study add to the currently available information by providing an overview of the impact of the work from home policy at PT Wilmar International on employees' working conditions. All of this will help business owners, human resource managers, and employees at PT Wilmar International to understand the benefits and risks of working from home so that they can know how to implement and manage it. This study has successfully identified possible areas for growth and has recommended potential routes.Keywords : Work From Home, Employee Performance